Analisa Kualitas Air Sungai Batang Idas Kecamatan Lubuk Kilangan Indarung Padang pada Bulan Desember 2011 dan Maret 2012 - Melisa Sri Hardianti; Indang Dewata; Hardeli Hardeli (Jurnal Periodic Jurusan Kimia UNP, 2012)
Has done research about determination water quality in Batang Idas River at December 2011 to Maret 2012 with purpose to knows degree of water pollution with doing analisys of temperature, DHL, TSS, TDS, pH, DO, BOD, COD, an analisys consentration of Fe, Ca, and Al metal in water and sediment. The next preposition with rule government number of 82, 2001th and it evaluated. Result of experiment look that weather sampling time can influence the result. I got some parameter concentration from low value to high value are temperature is 22-300C, pH is 6.1-8.6, DHL is 0.078-0.201 mS/cm, TSS is 108-6149 mg/l, TDS is 39-130.78 mg/l, DO is 7.39-12.73 mg/l, BOD is 0.65-2.17 mg/l, COD is 1.71-74.31 mg/l, Fe metal is 0.3-119.6 ppm,  Ca metal is 9.34-5371 ppm,  Al metal is 5.2-7.26 ppm, and total concentration metal in sedimentis 0.019-46.61 %.  The average concentration of some parameter exist under limit certainty rule government number of 82, 2001th except to COD in area 2, 3 and TSS in area 2, 3 and 4. Concentration of metal past over limit RMC (Recommendation Maximun Concentration for Water Irrigation). The conclusion that even increase concentration some parameter in mine area and followed increase concentration some parameter in Batang Idas River and in sail down than to rise.  The reason is waste from mine limestone area, activity of human, and erosion of land.